Lithium Hydroxide Assisted Endo‐Selective [4+4]‐Photocycloaddition of Pyran‐2‐ones. Issue 16 (9th April 2021) - Li, Lei; Turnbull, William L.; McDonald, Robert; West, F. G.
Abstract: 3‐Acyl‐4‐hydroxypyan‐2‐ones with pendent furans, readily available from dehydroacetic acid, are substrates for intramolecular [4+4]‐photocycloaddition. In the presence of stoichiometric lithium base, these substrates undergo conversion to lactone‐bridged cyclooctenones in moderate to good yields upon irradiation in THF at 0 °C. In contrast to other crossed [4+4]‐photocycloadditions of pyran‐2‐ones, these examples proceed with complete diastereoselectivity for the endo cycloadducts. Abstract : Readily accessible 3‐acyl‐4‐hydroxypyran‐2‐ones with pendent furans undergo [4+4]‐photocycloaddition reactions in the presence of lithium ion to afford lactone‐bridged cyclooctenones with complete selectivity for the endo cycloadducts.